Bioethanol and biodiesel: Bibliometric mapping, policies and future needs. (December 2021) - Osman, Ahmed I.; Qasim, Umair; Jamil, Farrukh; Al-Muhtaseb, Ala'a H.; Jrai, Ahmad Abu; Al-Riyami, Mohammed; Al-Maawali, Suhaib; Al-Haj, Lamya; Al-Hinai, Amer; Al-Abri, Mohammed; Inayat, Abrar; Waris, Ammara; et al.
Abstract: Rising demand for energy resources alongside climate emergency concerns has attracted the urgent attention of researchers towards the preparation and utilization of biofuels. This review will investigate the different generations of biofuels and more particularly, the developmental and production processes for creating liquid biofuels. Initially, the first-generation biofuel was dependent on edible resources, which has caused controversy and arguments on whether to fulfil the "food or fuel requirement" for civilization. Second-generation biofuels employed inedible resources, however, the cost of production at a commercial scale has restricted its expansion. Recently, third and fourth-generation use microorganisms and genetically modified microorganisms, respectively, to produce biofuels and create an efficient synthetic fuel switch route. Although the last two generations are still in the developmental phase, thorough research is required before commercial-scale production. In conclusion, this review has found that first- and second-generation biofuel production approaches will soon be inadequate to satisfy the exponentially rising demand for biofuels. Therefore, substantial research efforts currently and in the future should focus on the production of third and fourth-generation biofuels, especially on engineered microorganisms. Ultimately, the structure of this review is to outline the current state of the art research regarding biofuels, their production processes and limitations/challenges. This was done through critically reviewing the most up-to-date literature and utilizing bibliometric analysis tools to put forward the guidelines for the future routes of the four generations of biofuels. Graphical abstract: Image 1 Highlights: Biofuels have a significant responsibility in meeting the global energy requirements. Fourth generations still need developmental before its commercial-scale production. Large-scale biofuel production is urgent and entirely achievable to meet energy needs. Thermochemical conversion processes heavily outweigh physical one to produce biofuel.